A correlational study of hope and its relationship with spiritual health on hemodialysis patients - Nasrin Tavassoli; Azar Darvishpour; Roya Mansour-Ghanaei; Zahra Atrkarroushan (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: One of the main psychological problems in hemodialysis patients is hopelessness. Spiritual health leads the patients toward hope and goal in life. Given the importance of the issue and the little research in this area, this study aimed to assess hope and its relationship with spiritual health on hemodialysis patients in Rasht Razi Hospital of Iran. MATERIALS AND METHODS: This correlational study carried out on 103 patients who admitted in Rasht Razi Hospital Hemodialysis Center by simple random sampling. The data were collected through Snyder's Hope Scale and Spiritual Health. The psychomotricity of these questionnaires has been confirmed in domestic studies. The data were analyzed by using descriptive and inferential statistics (Pearson correlation coefficient). RESULTS: The majority of the patients were male (59.2%), in the age group of above 60 (46.60%), married (83.5%), with low income (60.2%), and under diploma (53.4%). The mean of hope score was 36.36 (±9.10) that showed the high level of hope in the majority of the patients. The mean of the total spiritual health score was 227.93 (±19.01) that indicates the high level of spiritual health in hemodialysis patients. There was a positive and significant correlation between spiritual health and its dimensions and hope (P < 0.05). CONCLUSIONS: The results of this study approve the importance of spiritual health as an effective variable on hope among hemodialysis patients. Hence, health-care providers and clinical experts are recommended to focus on spiritual health to increase hope among such patients.